Isolation, alkaline extraction, and characterization of starch from mango seeds for pharmaceutical applications - Meenakshi Bharkatiya; Pooja P. Dhanawade; Nitin H. Salunkhe (Creative Pharma Assent, 2026)
Background: Mango (Mangifera indica L.) seed is an abundant agro-waste with potential as a sustainable biopolymer source. This study explores the conversion of mango seed waste into high-purity starch and evaluates its physicochemical, structural, and functional properties for pharmaceutical applications. Methodology: The starch extracted from mango seeds by the alkaline method was subjected to phytochemical screening, physicochemical evaluation, flow property analysis, and advanced characterization techniques, including ATR-FTIR, NMR, SEM, XRD, DSC, and mass spectrometry. Results and discussion: The extraction process yielded 40% (w/w) starch. Phytochemical screening confirmed the exclusive presence of carbohydrates, indicating high purity. The starch exhibited a high amylopectin content (98.47%) and a low amylose content (1.53%), indicating a highly branched structure. Moisture content was low (0.80%), while the swelling index reached 180%, demonstrating excellent water absorption. The pH was slightly acidic (6.12 ± 0.07), and flow properties were acceptable based on bulk density, tapped density, Carr’s index, and Hausner’s ratio. SEM showed oval and irregular granules sized 10–22 μm. ATR-FTIR and NMR confirmed polysaccharide structures, XRD revealed A-type crystallinity, DSC showed thermal degradation at 326 °C with an enthalpy of 29.63 J/g, and mass spectrometry indicated glucose polymer fragmentation. Conclusion: Mango seed starch demonstrates high purity with trace residual lipids/proteins detected by spectroscopic analysis, favorable functional properties, and structural stability, supporting its potential as a sustainable and effective excipient for pharmaceutical formulations.